CGIAR’s GDI Matrix: Promoting Transparency and Accountability for Gender, Diversity and Inclusion in CGIAR workplaces - CGIAR System Organization (CGIAR System Organization, 2020)
The GDI Matrix has 15 performance indicators, aligned with CGIAR’s GDI Action Plan. Each indicator includes specific requirements which are measured by four progressive ratings. The four rating categories are: missing requirements, approaches requirements, meets requirements, exceeds requirements. The ratings allow CGIAR Centers and Alliances to self-assess and report, in an evidence-based manner, on their current performance level for each indicator, and to move progressively towards higher performance. The Matrix contains both activity-based and numerical results-based targets to ensure accountability for commitment to actions set out in the CGIAR GDI Action Plan and to measure the impact of actions taken.